Intercultural Conflict in the French Translation of Hrant Matevosyan's Novel “Autumn Sun”: Curses and Blessings - Sargsyan, Gayane (Translation Studies: Theory and Practice, 2021)
The objectives of this article are to relive the problems of translation of “culturemes”. In our research we focus on cultural translation, especially the issue of cultural inequivalences or losses occurring in the translation of curses and blessings in Hrant Matevosyan’s novel “Autumn Sun”.
Keywords: intercultural conflict; translation; realia; curses; blessings